Prevalence and factors associated with traditional herbal medicine use among patients on highly active antiretroviral therapy in Uganda - Namuddu, Betty; Kalyango, Joan N.; Karamagi, Charles; Mudiope, Peter; Sumba, Samwel; Kalende, Henry; Wobudeya, Eric; Kigozi, Brian K.; Waako, Paul (BMC Public Health, 2011)
In Africa, herbal medicines are often used as primary treatment for Human immunodeficiency virus (HIV) related problems. Concurrent use of traditional herbal medicines (THM) with antiretroviral drugs (ARVs) is widespread among HIV infected patients. However, the extent of THM use is not known in most settings in Sub- Saharan Africa. This study aimed at determining the prevalence and factors associated with THM use among HIV infected patients on highly active antiretroviral therapy (HAART) attending The AIDS Support Organization (TASO) in Uganda. TASO is a non-governmental organization devoted to offering HIV/AIDS care and treatment services in the population. Methods: This was a cross-sectional study carried out in two TASO treatment centres in Uganda among 401 randomly selected eligible participants. We included participants who were 18 years and above, were enrolled on HAART, and consented to participate in the study. Data was collected using an interviewer-administered semistructured questionnaire. THM use referred to someone who had ever used or was currently using herbal medicine while on highly active antiretroviral therapy (HAART) by the time of the study. Data was captured in Epi-data version 3.1 and exported to STATA version 9.0 for analysis. Results: The prevalence of THM use was 33.7%. Patients on HAART for < 4 years were more likely to use THM (OR = 5.98, 95% CI 1.13 - 31.73) as well as those who experienced HAART side effects (OR = 3.66, 95% CI: 1.15 - 11.68). Older patients (≥39 years) were less likely to use THM (OR = 0.26 95% CI: 0.08 - 0.83). Participants with HAART adherence levels > 95% were less likely to use THM (OR = 0.09, 95% CI 0.01 - 0.65). Conclusion: The prevalence of THM use among participants on HAART was high. This raises clinical and pharmacological concerns that need attention by the health care service providers.
Keywords: Prevalence; Traditional herbal medicine; Patients; Antiretroviral therapy; Uganda